A new calculation method of water vapor transfer properties of fabrics from upright cup method. Issue 4 (2nd April 2016) - Huang, Jianhua; Li, Wenbin
Abstract : In view of the fact that the water vapor transmission rates derived from the upright cup method were not very well correlated with those from other methods. The water vapor transfer properties of 9 fabrics were measured by using the upright cup method. The intrinsic water vapor diffusion resistance was calculated for expressing the water vapor transfer behavior and compared with those from the sweating guarded hot plate method, the desiccant inverted cup method, and the dynamic moisture permeation cell method. The following statistical analysis indicated that the upright cup method had statistically significant correlation with the other three methods. Therefore, the water vapor diffusion resistance should be chosen to characterize the water vapor transfer properties of fabrics.